Interview with the General Secretaries of the Students Union Juan Ignacio Ramos (1987-1991) and Bárbara Areal (1994-1998) - González-Moreno, Javier (Historia y Memoria de la Educación, 2022)
This 2021-2022 academic year marks the 35th anniversary of the student strike of the 1986-1987 academic year, which constitutes the largest student conflict in the history of Spain. It marked the beginning of a three-year period of protests against the policies of the PSOE government, which had failed to satisfy the workers’ expectations of reform. These protests went in crescendo with the teachers’ strike of the 1987-1988 academic year, culminating in the historic general strike of December 14, 1988. The student strike of 1986-1987 stood out for its massive participation and for the important effects it achieved in educational policy, especially in the extension of secondary education. The fundamental organization of these protests was the responsibility of the Student Union. We chat here about these events and about the subsequent trajectory of the Student Union with Juan Ignacio Ramos, its general secretary at the time, and with Bárbara Areal, a militant in that strike who later became general secretary.